Preventive Maintenance CNC Machine DMC 210U - Prasetya, Ramadhani; Darul, Samsul; Suryaman, Nia Nuraeni; Firdaus3, Abdul Rohman; Kopah (International Journal of Psychosocial Rehabilitation, 2020)
Maintenance is an activity to maintain or maintain factory equipment and carry out repairs or adjustments and replacements needed so that there is a satisfactory state of production operation in accordance with what is planned. The purpose of maintenance: to keep the existing system running as it should and also to be able to control costs both for prevention and repairs in case of damage. The portal series type machine of DMC 210 U is a large, 5 axis / 5 axis machine that uses a stable bridge type structure to achieve high accuracy and dynamic performance. This model allows 5-axis / 5-axis machining with one arrangement, contributing to the increase in customer productivity, which is equipped with a high-speed pallet converter, which allows the operator to make arrangements for the next process during the production process. The methodology used in this study is to follow the stages of the process of preventive maintenance carried out on the DMC 210U CNC machine. Based on the results of handling including the Electronic and control systems, Axis, Spindles, APCs, ATCs, Hydrolic Units, Lube and Coolants, Cooling Systems, and Pneumatic Units, it can be concluded that the DMC 210 U CNC Machine is in good condition in the sense of not experiencing damage